TEACHER’S FEEDBACK THROUGH INSTAGRAM TO IMPROVE EFL VOCATIONAL HIGH SCHOOL STUDENTS’ WRITING RECOUNT TEXT - Gina Julianti (Journal of English Education Program (JEEP), 2020)
The present study is aimed at finding out whether or not teacher’s feedback through Instagram improve on the students’ writing recount text and to investigate the students’ perceptions on teacher’s feedback through Instagram in teaching writing recount text. The present study implemented a mixed-method with the type of true-experimental pre-test post-test control group design for the quantitative data and descriptive analysis for the qualitative data. The sample of the present study involved 24 students as the experimental and control group. Students’ document tests were used to obtain the data. Based on the statistical result, after teacher’s feedback through Instagram was implemented on students’ writing recount text especially personal recount text, the t-observed value was higher than t-table value; thereby, the null hypothesis (H0) was rejected and the alternative hypotheses (H1) was accepted. Thus, teacher’s feedback through Instagram is seen to be the whole activities of writing personal recount text are well improved. In addition, from the analysis content of students’ document test indicated significant progress in writing recount text. The students’ perception on teacher’s feedback through Instagram in teaching writing of recount text that the students think they always pay attention to the errors identified by the teacher on their writing and try to fix all of them.  Based on the findings, it is recommended for English teachers to apply technology such Instagram and teacher’s feedback trough Instagram, especially in teaching writing so that the students' writing can be improved.Keywords: Teacher writing feedback, Instagram, Vocational HighSchool, writing, and recount text.